Palk Bay fishing problem requires Indo-Sri Lankan joint-governance. (2nd July 2020) - Vincent, S.
ABSTRACT: Palk Bay (PB) is an inlet in the Bay of Bengal. The 1974 Indo-Sri Lankan agreement that delimited the International Maritime Boundary Line (IMBL) in PB, brought Kachchu Thivu under sovereignty of Sri Lanka, thus limiting the fishing ground for Indian fishers. Indian fishers allege that their traditional fishing right in PB, recognised by the 1974 agreement, was cancelled by the subsequent 1976 Indo-Sri Lankan agreement. Presently 2650 Indian trawlers are fishing in PB, often in Sri Lankan waters. They are repeatedly attacked by the Sri Lanka navy. The Government of India has been initiating programmes to prevent the trans boarder fishing and to divert the mechanized trawlers for deep-sea fishing. Indian fishers demand the retrieval of Kachchu Thivu and the restoration of traditional fishing rights as the permanent solution. The study reveals that the perspectives and the programmes of the Government cannot solve the problem and also the demands of the fishers are not legally feasible. So joint governance and management of PB by both countries is proposed as a lasting solution.